The self in transformation - Solomon, Hester (Karnac, 2007)
This book brings together into one volume a number of articles that the author has written over the past 20 years, and includes a new extended essay written especially for this volume. The chapters, organized into sections, explore theoretical and clinical matters within a Jungian analytical framework, making carefully considered links to a number of psychoanalytical themes and concepts. The book also includes a section on ethics in the consulting room. In her new essay, Hester Solomon discusses pivotal themes in depth psychology: psychic transformation, synchronicity, and the emergence of com.